2022
DOI: 10.1007/s00787-022-01973-0
|View full text |Cite
|
Sign up to set email alerts
|

Perpetrators and victims of cyberbullying among youth with conduct disorder

Abstract: Due to modern technological innovations, aggressive behaviors have expanded into the cyberspace, creating a new matter of public concern: cyberbullying. Antisocial and aggressive behaviors, including bullying are characteristic for children and adolescents diagnosed with conduct disorder (CD), raising the question whether these youths are highly involved in cyberbullying experiences, too. 206 participants with CD versus typically developing controls (TDCs) aged 9–19 years (57% girls) were included in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…In recent years, especially after the pandemic, there has been an increase in the use of smartphones over overs devices among young people. Regarding the association between cyberbullying and mental health, our ndings support the evidence that victims of cyberbullying have more emotional problems, such as depression (54,55) and anxiety (56), and perpetrators have a higher risk of conduct problems (57). Fewer studies have explored the association between cyber victimization or perpetration and empathy and prosocial skills (58).…”
Section: Discussionsupporting
confidence: 79%
“…In recent years, especially after the pandemic, there has been an increase in the use of smartphones over overs devices among young people. Regarding the association between cyberbullying and mental health, our ndings support the evidence that victims of cyberbullying have more emotional problems, such as depression (54,55) and anxiety (56), and perpetrators have a higher risk of conduct problems (57). Fewer studies have explored the association between cyber victimization or perpetration and empathy and prosocial skills (58).…”
Section: Discussionsupporting
confidence: 79%
“…A literature review revealed that sex and academic performance in the background variable, as well as social status and ICT use, correlate with and predict cyberbullying; sex predicts cyberbullying [ 35 ], with men being more likely to be cyberbullies than women [ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. Furthermore, female sex is a stronger predictor of cyberbullying victimization [ 43 ] and bystander behavior than male [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In more severe cases, extreme behaviors, such as outbursts of anger, starting fires, and harming animals or other children, can be observed (Mohamed 2022, Yücel 2020. Although these behavioral problems can be observed in various environments, Baumann et al (2022) addressed a different point in a study that examined the cyberbullying experiences of individuals with conduct disorders. Accordingly, it has been revealed that individuals with conduct disorders can be either perpetrators or victims of cyberbullying (Bauman et al 2022).…”
Section: Introductionmentioning
confidence: 99%